Narasi Budaya dan Ketahanan Komunal: Eksplorasi Makna Simbolik Spanduk Berbahasa Jawa pada Pandemi Covid- 19 - Kertamukti, Rama Kertamukti; Nashira, Khalifa Zia (Program Studi Ilmu Komunikasi, 2024)
This study analyses the symbolic meaning of Javanese banners warning of the danger of COVID-19 in Yogyakarta using Roland Barthes' semiotic theory. The analysis includes three stages: denotation, connotation and myth. The messages on the banners contain clear literal meanings about lockdowns and the coronavirus, and reflect people's frustrations and concerns about social restrictions. At the mythic level, the banners reinforce cultural narratives of resilience and communal co-operation. Javanese society has a long-standing culture. The use of Javanese language demonstrates an emphasis on local values and strengthens community ties. This study confirms the importance of health communication that resonates with local culture in improving community adherence to health measures. These messages not only disseminate information but also shape collective identity amidst the pandemic.